Studying Maximum Plantar Stress per Insole Design Using Foot CT-Scan Images of Hyperelastic Soft Tissues - Ali Sarikhani; Abbas Motalebizadeh; Sasan Asiaei; Babak Kamali Doost Azad (Applied Bionics and Biomechanics)
The insole shape and the resulting plantar stress distribution have a pivotal impact on overall health. In this paper, by Finite Element Method, maximum stress value and stress distribution of plantar were studied for different insoles designs, which are the flat surface and the custom-molded (conformal) surface. Moreover, insole thickness, heel’s height, and different materials were used to minimize the maximum stress and achieve the most uniform stress distribution. The foot shape and its details used in this paper were imported from online CT-Scan images. Results show that the custom-molded insole reduced maximum stress 40% more than the flat surface insole. Upon increase of thickness in both insole types, stress distribution becomes more uniform and maximum stress value decreases up to 10%; however, increase of thickness becomes ineffective above a threshold of 1 cm. By increasing heel height (degree of insole), maximum stress moves from heel to toes and becomes more uniform. Therefore, this scenario is very helpful for control of stress in 0.2° to 0.4° degrees for custom-molded insole and over 1° for flat insole. By changing the material of the insole, the value of maximum stress remains nearly constant. The custom-molded (conformal) insole which has 0.5 to 1 cm thickness and 0.2° to 0.4° degrees is found to be the most compatible form for foot.